Case Analysis Of Revenue Recognition Fraud Of Pt Garuda Indonesia (Persero) Tbk In 2018 - Made Hari Prayoga; Dyah Purwanti (Kesatuan Press, 2020)
The purpose of this study is to analyze cases of revenue recognition fraud at PT Garuda Indonesia that occurred for the 2018 financial statements. This case attracted public attention because PT Garuda as one of the leading state-owned airlines in Indonesia is known for its service performance. In order to achieve our research objectives, we investigated these fraud cases with a qualitative approach. The findings of the study are that PT Garuda Indonesia committed fraud by acknowledging compensation income for the right to install connectivity and entertainment service equipment on board and content management from the agreement with PT Mahata Aero Teknologi in the consolidated financial statements of PT Garuda Indonesia (Persero) Tbk in 2018. Action This is an intent or negligence and is included in the cook the book scheme, namely recognizing income before it can be recognized. Fraud is driven by industrial pressures in the form of unfavorable industrial conditions and financial pressures in which companies try to book maximum profits in order to achieve the target set. The result of the action is that the resulting financial statements are materially misleading.